Movies About the Movies : Hollywood Reflected - Ames, Christopher (Book collections on Project MUSE., 2015)
Hundreds of Hollywood-on-Hollywood movies can be found throughout the history of American cinema, from the days of silents to the present. They include films from genres as far ranging as musical, film noir, melodrama, comedy, and action-adventure. Such movies seduce us with the promise of revealing the reality behind the camera. But, as part of the very industry they supposedly critique, they cannot take us behind the scenes in any true sense. Through close analysis of fifteen critically acclaimed films, Christopher Ames reveals how the idea of Hollywood is constructed and constructs itself.